Durable Clinical Benefit after Dual Checkpoint Inhibition and Single-agent Nivolumab Following Pembrolizumab Failure in Mismatch Repair-deficient Colon Cancer - Yat-Fung Chow; Hou-Hsuan Cheng; Ming-Huang Chen (Journal of Cancer Research and Practice)
Immunotherapy with immune checkpoint inhibitors (ICIs) is beneficial in treating tumors with high microsatellite instability or DNA mismatch repair deficiency (dMMR) tumors. However, the ideal therapy for patients with advanced dMMR cancer after the failure of the first ICI regimen remains unclear. This case report describes a patient with dMMR ascending colon cancer who later developed endometrial cancer. The patient underwent a sequence of immunotherapies, starting with pembrolizumab, followed by a combination of ipilimumab and nivolumab and finally single-agent nivolumab. This sequence led to a prolonged period of disease control exceeding 20 months. The case highlights the potential benefits of dual checkpoint inhibition and sequential ICI regimens in managing advanced dMMR tumors even after first-line ICI failure; this combination is a promising strategy to explore in future research.